1994
DOI: 10.5694/j.1326-5377.1994.tb126597.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal endoscopy in central Australian Aborigines

Abstract: Objectives: To examine the upper gastrointestinal endoscopic findings in Australian Aborigines in central Australia; to determine if peptic ulceration occurs in this group; and to discover whether this population shares Helicobacter pylori as a risk factor for peptic ulceration.Methods: A retrospective analysis of the records of all Aboriginal patients undergoing endoscopy at a general hospital over a two-year period.Results: Eighty-five endoscopies were performed in 64 patients. Haematemesis and melaena was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Similarly, a 1988 serological study of north‐east Arnhem Land communities showed that less than 1% of those tested had evidence of the infection 6 . In 1994, a retrospective review carried out in Alice Springs found that upper gastrointestinal endoscopies were performed far less frequently in Indigenous patients 7 . Nevertheless, 14% of Indigenous patients who underwent gastroscopy had peptic ulcers, 36% had evidence of gastritis or duodenitis, and one had a malignant ulcer.…”
mentioning
confidence: 99%
“…Similarly, a 1988 serological study of north‐east Arnhem Land communities showed that less than 1% of those tested had evidence of the infection 6 . In 1994, a retrospective review carried out in Alice Springs found that upper gastrointestinal endoscopies were performed far less frequently in Indigenous patients 7 . Nevertheless, 14% of Indigenous patients who underwent gastroscopy had peptic ulcers, 36% had evidence of gastritis or duodenitis, and one had a malignant ulcer.…”
mentioning
confidence: 99%
“…Patients with non-GI related conditions, for example coronary heart disease ( Coles et al, 2003 ), diabetes ( Schimke et al, 2009 ), sudden infant death syndrome (SIDS) ( Ho et al, 2001 ), multiple sclerosis ( Pedrini et al, 2015 ) and HIV/AIDS ( Edwards et al, 1991 ) were also commonly investigated. Specific cultural groups studied included both urban and rural Aboriginal populations (8.0% of the included publications) ( Windsor et al, 2005 ; Dwyer et al, 1988b ; Pringle et al, 2015 ; Mollison et al, 1994 ; McDonald et al, 2004 ; Ritchie et al, 2009 ), newly arrived migrants (10.6% of included studies) ( Dwyer et al, 1988a ; Gibney et al, 2009 ; Chaves et al, 2009 ; Cherian et al, 2008 ; Mutch et al, 2012 ; Johnston, Smith & Roydhouse, 2012 ; Abdul Rahim et al, 2017 ; Benson, Rahim & Agrawal, 2017 ), ethnic groups such as members of the Chinese population of Melbourne (2.6% of included studies) ( Chow et al, 1995 ; Lin et al, 1991 ), and institutionalised populations (2.6% of included studies) ( Lambert et al, 1995 ; Wallace, Webb & Schluter, 2002 ). Several studies investigated groups of health professionals, hypothesised to be at greater risk of contracting H. pylori , including dentists ( Lin et al, 1998b ) gastroenterologists ( Lin et al, 1994 ) and nurses ( Robertson, Cade & Clancy, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…Male AIDS patients ( Edwards et al, 1991 ) and females with multiple sclerosis ( Pedrini et al, 2015 ) were also found to have a low prevalence of H. pylori infection. Gastric cancer patients ( Dugué et al, 2019 ; Mitchell et al, 2008 ), institutionalised individuals ( Lambert et al, 1995 ; Wallace, Webb & Schluter, 2002 ), refugees ( Chaves et al, 2009 ; Cherian et al, 2008 ; Johnston, Smith & Roydhouse, 2012 ) and Aboriginal and Torres Strait Islander populations ( Windsor et al, 2005 ; Mollison et al, 1994 ; McDonald et al, 2004 ) typically had high prevalence of H. pylori infection. Recent prevalence estimates are lacking for vulnerable groups.…”
Section: Resultsmentioning
confidence: 99%